Calculating the Moduli Elasticity for Reinforced Concrete Using New Rule of Mixtures Approach for the Dam Structure - Zulkefli Z.F.; Zawawi M.H.; Hassan N.H.; Zainol M.R.R.M.A.; Abas M.A.; Mazlan A.Z.A. (EDP Sciences, 2023)
Accident prevention; Dams; Elasticity; Electric power systems; Flood control; Mixtures; Reinforced concrete; Safety engineering; Software reliability; Stiffness; Stress-strain curves; System theory; Bureau of reclamations; Concrete properties; Destructive; High-risk structures; Non destructive; Reliability monitoring; Rules of mixture (Rom); Solid works; Concrete mixtures